Monitoring immunological COVID-19 vaccine clinical testing across the CEPI Centralized Laboratory Network - Schwartz, Lauren M.; Vila-Belda, Jose; Carless, Jerome; Dhakal, Sadish; Hostyn, Koen; Gorman, Trina; Ogbeni, Deborah; Kamuyu, Gathoni; Manak, Mark; Bernasconi, Valentina; Azizi, Ali (Frontiers in Immunology, 2025)
The CEPI-Centralized Laboratory Network (CLN) has significantly contributed to the development of several approved SARS-CoV-2 vaccines by conducting over 70,000 clinical samples for testing from various vaccine developers. A centralized data management system was developed to track, review, store and share immunological clinical results generated from sample testing. The data system ensures the completeness and accuracy of submitted results and checks the set criteria in controls for each assay. Each testing facility within the network submits their results to a secure storage system using report forms with embedded data quality checks. Upon submission, a statistical program runs additional checks to identify errors in completeness and uniqueness. Any discrepancies or errors are shared with the testing facility to rectify. Reports are further reviewed by CEPI-CLN experts before releasing to the vaccine developer. Study results are then consolidated into an internal relational database management system, enabling CEPI to analyze the data through an interactive dashboard that visualizes control trends and sample results across all studies. This analysis facilitates the harmonization of immunological data and helps to inform CEPI’s programmatic and strategic decision making. Given the success of this approach with SARS-CoV-2 vaccines, the system will be adopted for new pathogens and assay types currently under development at CEPI-CLN.